-2(x-5)+8x=9x-6

Simple and best practice solution for -2(x-5)+8x=9x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-5)+8x=9x-6 equation:


Simplifying
-2(x + -5) + 8x = 9x + -6

Reorder the terms:
-2(-5 + x) + 8x = 9x + -6
(-5 * -2 + x * -2) + 8x = 9x + -6
(10 + -2x) + 8x = 9x + -6

Combine like terms: -2x + 8x = 6x
10 + 6x = 9x + -6

Reorder the terms:
10 + 6x = -6 + 9x

Solving
10 + 6x = -6 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
10 + 6x + -9x = -6 + 9x + -9x

Combine like terms: 6x + -9x = -3x
10 + -3x = -6 + 9x + -9x

Combine like terms: 9x + -9x = 0
10 + -3x = -6 + 0
10 + -3x = -6

Add '-10' to each side of the equation.
10 + -10 + -3x = -6 + -10

Combine like terms: 10 + -10 = 0
0 + -3x = -6 + -10
-3x = -6 + -10

Combine like terms: -6 + -10 = -16
-3x = -16

Divide each side by '-3'.
x = 5.333333333

Simplifying
x = 5.333333333

See similar equations:

| (8+6i)+(4-3i)=0 | | 109-3x=15x-21 | | 3x-5=4x-2 | | -15+n=-27 | | -2x-58=2-4x | | -x/6 | | 3-4-6/x=12 | | 5-3x=2x+9+3x | | 2(7bx+y)=13bx-3y | | 20+4x=30 | | -3x+6-1=12 | | 4-1-2y=8 | | -2x+14=-16 | | -2x+(-24)=-18 | | 2/3x-1/6=-7 | | -6(10-4x)=3(-12-8x) | | x=23-5y | | -3x-13=-4 | | 18=0.6g | | 4*2-2y=8 | | 6-=2x | | 5x+25=15x-15 | | 8(n+3)-2(3n-4)=31 | | 8x+3y=-38 | | 2.4-0.7x=3 | | -6x+(-9)=3 | | 6p-13=17 | | -8.4x=-39-1.9x | | x-=-9 | | 9/5=x/4 | | -6+x=-3 | | 10/n=3/7 |

Equations solver categories